Unraveling cancer progression pathways and phytochemical therapeutic strategies for its management - Sharma, Vikas; Chaudhary, Anis Ahmad; Bawari, Sweta; Gupta, Saurabh; Mishra, Richa; Khan, Salah-Ud-Din; Ali, Mohamed A. M.; Shahid, Mohammad; Srivastava, Saurabh; Verma, Devvrat; Gupta, Arti; Kumar, Sanjay; et al. (Frontiers in Pharmacology, 2024)
Cancer prevention is currently envisioned as a molecular-based approach to prevent carcinogenesis in pre-cancerous stages i.e., dysplasia and carcinoma in-situ. Cancer is the second leading cause of mortality worldwide and a more than 61% increase is expected by 2040. Detailed exploration of cancer progression pathways including NF-kβ signalling pathway, Wnt-B Catenin signalling pathway, JAK-STAT pathway, TNF-α mediated pathway, MAPK/mTor pathway, apoptotic and angiogenic pathway; and effector molecules involved in cancer development have been discussed in the manuscript. Critical evaluation of these effector molecules through molecular approaches using phytomolecules can intersect cancer formation and its metastasis. Manipulation in effector molecules like levels of NF-kβ, SOCS, β-catenin, BAX, BAK, VEGF, STAT, Bcl2, p53, caspases, CDKs have played an important role in inhibiting tumour growth and it's spread. Plant derived secondary metabolites obtained from natural sources have been extensively studied for its cancer preventing potential in las few decades. Eugenol, anethole, capsaicin, sanguinarine, EGCG, 6-gingerol and resveratrol are some of the examples of such interesting lead molecules and mentioned in the manuscript. This work is an attempt to put up a comprehensive approach in understanding cancer progression pathways and their management using effector herbal molecules. The role of different plant metabolites with their chronic toxicity profiling in modulating cancer development pathways has also been highlighted.